EDUCATIONAL LOGISTICS AS ONE OF METHODS OF TECHNOLOGY TEACHERS’ MASTERY INCREASING IN POSTGRADUATE EDUCATION - Armeisky, O . S. (Problems of Engineer-Pedagogical Education, 2018)
In the article the essence of teaching logistics as one of the methods for improving the skills of teachers school subject "Technology" general education zakladivu current conditions; are prerequisites for their formation; The features of the flow of knowledge and its accumulation on a global scale; The features of logistics as a science of planning, organization, management, control and regulation of the movement of material and information flows in space and time from their primary source to the end user; and singled out approaches to improve the quality control of acquired knowledge. The article shows that logistics offers process control spending, namely by determining the initial, intermediate and final level of knowledge of testing after studying each section surveys the classroom, conducting monitoring studies, surveys and diagnostics. Outlined the specific teaching methods and tools of logistics, which allows to open the way for creative self-realization and effective pedagogical activity of teachers of secondary schools.